STRUCTURAL DESIGN OF CONTAINER BERTH NO. 2 STAGE 1 PHASE 2 AT PORT OF PATIMBAN, SUBANG, WEST JAVA - Herfrison, Aditya
Indonesia is an archipelagic country that relies on maritime transportation for the distribution of goods. Currently, Indonesia still lacks port capacity, resulting in high logistics costs. Through the Presidential Decree of The Republic of Indonesia Number 47 Year 2016, the government decided the Patimban Port located in Subang Regency, West Java as a representative location for the construction of a new port. This Final Project will discuss the structural design of container berth no. 2 phase 1-2 at Port of Patimban. The design data was obtained from the Patimban Port Master Plan (KP 87 of 2017) and the available environmental data. The data is then used to calculate loads acting on the berth. The berth structure is designed based on the loads on the berth and refers to port design code and standards. The structure design was then analyzed using SAP2000 with LRFD and ASD load combination. The structure is then optimized until the UCR value of model is more than 0.8 and less than 1.0. The results of the model in the form of internal forces within structural elements and joint reactions are then used for the design of structural reinforcement and the analysis of load-carrying capacity.